2011
DOI: 10.14723/tmrsj.36.371
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasmin Treatment on the Fibrin Gel Formation

Abstract: In order to clarify the effective regions that are substantially involved in the gelling process of plasma glycoprotein fibrinogen, we examined the aggregating properties of plasmin-treated fibrinogen, fragment-X. Two types of fragment-X were prepared by the digestion at 6 o C and 37 o C (fragment-XY and -XN, respectively). αC regions were cleaved thoroughly in both samples, but the amount of cleavage of BβN region differed between them (higher in the fragment-XN). Thrombin-and reptilase-catalyzed fibrin polym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…The αC region could play a role to mediate those interactions effectively in a complimentary manner. In agreement with this scenario, abnormal fibrin oligomers are formed in the fibrinogen lacking BβN region [23], and lateral aggregation does not proceed at all in the fibrinogen lacking both of the BβN and αC regions [9,25].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…The αC region could play a role to mediate those interactions effectively in a complimentary manner. In agreement with this scenario, abnormal fibrin oligomers are formed in the fibrinogen lacking BβN region [23], and lateral aggregation does not proceed at all in the fibrinogen lacking both of the BβN and αC regions [9,25].…”
Section: Discussionmentioning
confidence: 83%
“…This is the first step of the fibrin polymerization, and the motive force of this step is the specific interaction between A-knob in the central E region and a-hole in the distal D region. In the successive second step, grown protofibrils aggregate laterally resulting in the fiber bundles and network formation, although little is known about the detailed mechanism of lateral aggregation [7][8][9]. Fibrin network plays an indispensable role in the hemostasis, wound healing, and thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Variant fibrinogen, where deletion of the sequence Bβ9-72 occurs, shows seriously impaired dysfibrinogenemia [8]. No fibrin polymerization is observed by throm-bin nor reptilase in the fibrinogen, of which Bβ1-133 is deleted, although protofibril formation occurs [4]. The results that reptilase-catalyzed fibrin polymerizationis in intact one were affected by Clconcent-ration similarly to those of thrombin-catalyzed one, suggests that the entity of BβN region, neither fibrinopeptide B nor B-knob alone, could be involved in the lateral aggregation dominantly by interacting with D region.…”
Section: Discussionmentioning
confidence: 99%
“…In the successive second step, protofibrils grown axially aggregate laterally resulting in the fiber bundles and fibrin clot. Although little is known about the detailed mechanism of lateral aggregation, it has been suggested that the interaction between amino terminal region of Bβ chain (BβN region) and the D region plays an important role in aggregating laterally [3,4]. BβN region is released succeeding to the protofibril formation and the release might be controlled inhibitedly by CHO chains linked to Bβ chain at the D region of adjacent fibrin in the protofibril.…”
Section: Introductionmentioning
confidence: 99%